Evaluating the role of body size and habitat type in movement behavior in human‐dominated systems: A frog's eye view. Issue 6 (22nd June 2022) - Murphy, Mason; Boone, Michelle
Abstract: Animal movement is a key process that connects and maintains populations on the landscape, yet for most species, we do not understand how intrinsic and extrinsic factors interact to influence individual movement behavior. Land‐use/land‐cover changes highlight that connectivity among populations will depend upon an individual's ability to traverse habitats, which may vary as a result of habitat permeability, individual condition, or a combination of these factors. We examined the effects of intrinsic (body size) and extrinsic (habitat type) factors on desiccation tolerance, movement, and orientation in three anuran species (American toads, Anaxyrus americanus ; northern leopard frogs, Lithobates pipiens ; and Blanchard's cricket frogs, Acris blanchardi ) using laboratory and field studies to connect the effects of susceptibility to desiccation, size, and movement behavior in single‐habitat types and at habitat edges. Smaller anurans were more vulnerable to desiccation, particularly for species that metamorphose at relatively small sizes. Habitat type had the strongest effect on movement, while body size had more situational and species‐specific effects on movement. We found that individuals moved the farthest in habitat types that, when given the choice, they oriented away from, suggesting that these habitats are less favorable and could represent barriers to movement. Overall, our work demonstrated that differences in habitat type had strong impacts on individual movement behavior and influenced choices at habitat edges. By integrating intrinsic and extrinsic factors into our study, we provided evidence that population connectivity may be influenced not only by the habitat matrix but also by the condition of the individuals leaving the habitat patch. Abstract : We examined the effects of intrinsic (body size) and extrinsic (habitat type) factors on desiccation tolerance, movement, and orientation in three anuran species using a combination of laboratory desiccation trials and field studies to disentangle the individual and combined effects of these factors on movement. Habitat type had the strongest effect on movement, while body size had more situational and species‐specific effects on movement. We found that the habitats that most individuals oriented away from were the ones in which that same species moved the farthest, suggesting that this habitat is less favorable and could represent a barrier for movement.